Portfolio allocation as the president's calculations: loyalty, copartisanship, and political context in South Korea - Lee, Don S. (Cambridge University Press, 2018)
How do the president's calculations in achieving policy goals shape the allocation of cabinet portfolios? Despite the growing literature on presidential cabinet appointments, this question has barely been addressed. I argue that cabinet appointments are strongly affected not only by presidential incentives to effectively deliver their key policy commitments but also by their interest in having their administration maintain strong political leverage. Through an analysis of portfolio allocations in South Korea after democratization, I demonstrate that the posts wherein ministers can influence the government's overall reputation typically go to nonpartisan professionals ideologically aligned with presidents, while the posts wherein ministers can exert legislators' influence generally go to senior copartisans. My findings highlight a critical difference in presidential portfolio allocation from parliamentary democracies, where key posts tend to be reserved for senior parliamentarians from the ruling party.